2009
DOI: 10.14723/tmrsj.34.497
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-Metal-Anion Adsorption and Desorption Properties of <i>N,N</i>-Dimethylaminoethylacrylamide/Acrylamide Gels

Abstract: The authors have investigated heavy-metal-anion (hexavalent chromium, Cr(VI)) adsorption and desorption properties of N,N-dimethylaminoethylacrylamide/acrylamide (DMAEAAm/ AAm) gels successively. Though the DMAEAAm/AAm gels show relatively low Cr(VI)-capturing efficiencies, the hydrogels have a possibility of actual use as a heavy-metal-anion recovering material because the DMAEAAm/AAm gels with some compositions show high desorption efficiency of the captured-Cr(VI), which is advantageous to a heavy-metal-ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Therefore, the authors also carried out a couple of consecutive measurements of adsorption by and desorption from respective positively [14,15,17,18,21] ionized hydrogels and negatively [19][20][21] polarized ones in order to examine the possibility of the reuse of the hydrogel; and it was demonstrated that these hydrogels can be satisfactorily utilized in the heavy-metal and rare-metal recycle. Though the utilization of hydrogels for the recovery of heavy metals and rare metals seems to be promising judging from the previous and present experimental results, however, the assumed conditions in these studies were still too simple compared with those in actual waste processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the authors also carried out a couple of consecutive measurements of adsorption by and desorption from respective positively [14,15,17,18,21] ionized hydrogels and negatively [19][20][21] polarized ones in order to examine the possibility of the reuse of the hydrogel; and it was demonstrated that these hydrogels can be satisfactorily utilized in the heavy-metal and rare-metal recycle. Though the utilization of hydrogels for the recovery of heavy metals and rare metals seems to be promising judging from the previous and present experimental results, however, the assumed conditions in these studies were still too simple compared with those in actual waste processing.…”
Section: Discussionmentioning
confidence: 99%
“…In the authors' previous studies, measured were the heavy metal capturing efficiencies both of the positively [9,10,17,18,21] and negatively [11][12][13][14][15][16][19][20][21] ionized hydrogels: The heavy-metal cation capturing efficiency of sodium acrylate/acrylamide (SA/AAm) and carboxymethylcellulose (CMC-Na) gels were found to be ~20 wt% of network polymer [9] [10,21]. As for the heavy-metal-anion capturing hydrogels [11][12][13][14][15][16][19][20][21], their capturing efficiencies are larger than those of SA/AAm and CMC-Na gels, which are much larger than those of zeolites and ion-exchange resins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the detector was not able to show how much the heavy-metal amount the gel can adsorb. In these circumstances, the authors have been focusing attention on the adsorbable quantity of the heavy-metal-capturing gels aiming at the realizetion of the high-efficient heavy-metal recovery gels [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the heavy-metal-cation capturing hydrogels, the authors have been also investigating heavy-metalanion capturing hydrogels because there are many harmful heavy-metal anions in the environment such as Cr 2 O 7 2-; and they found that some heavy-metal-anion adsorbing hydrogels show larger heavy-metal capturing efficiencies than SA/AAm and CMC-Na gels [9][10][11][12][13][14]. Moreover, recently, the authors demonstrated the possibility of the high-efficient heavy-metal-recycle process utilizing these hydrogels [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%